Repetitive Behaviours and Restricted Interests in Individuals with Down Syndrome—One Way of Managing Their World? - Sheila Glenn (Brain Sciences, 2017)
This paper argues that the repetitive behaviour and restrictive interests (RBRI) displayed by individuals with Down syndrome have mostly positive functions. However, as research has developed from interests in Obsessional Compulsive Disorder or Autistic Spectrum Disorder, unfortunately a view has arisen that RBRI in individuals with Down syndrome are also likely to be pathological. This is particularly the case in adults. The paper reviews: (a) measures employed and the perspectives that have been used; (b) the development in typically developing individuals, those with Down syndrome, and those with other conditions associated with intellectual disability; (c) positive and possible negative effects of RBRI; and (d) the need for more research. The conclusion is that, for their level of development, RBRI are helpful for most individuals with Down syndrome.